Ascaris suum: molecular cloning of an intermediate filament - Bisoffi, Marco; Betschart, Bruno (My University, 1996)
It has been proposed that intermediate filament proteins are involved in force transduction from the muscle cells through the hypodermis to the cuticle of nematodes. An additional role of intermediate filaments as excretory/secretory components of parasitic nematodes is under discussion. We report on the molecular characterization of the cDNA clone AsIF of the intestinal nematode parasite Ascaris suum, encoding a member of the intermediate filament protein family by sequence comparison with intermediate filaments of other nematodes. We also show the precise location of the product encoded by AsIF within the organism by immunoelectron microscopy.
Keywords: Ascaris suum; intermediate filament proteins; molecular cloning; cDNA